A new obligation for companies in Spain: working time registration. Innovation or regression? - Sagardoy de Simón, Iñigo (2020)
The new Spanish regulation establishing compulsory hourly registration systems for employees in all types of companies and activities is generating intense debate about its practical usefulness and, above all, whether it goes against the new forms of employment and the flexibility the new world of work/employment world is demanding.